上肢機能障害を改善させるための工夫 - 鈴木, 俊明; 井尻, 朋人 (関西理学療法, 2022)
The important points for improvement of functional impairment of the upper limb are clarification of the impairment level and identification of the tissue related to the impairment. Also, we have to estimate the impairment not only from the perspective of the upper limb, but also from a whole-body viewpoint including the trunk and lower limbs. This paper presents the author's approaches for improving functional impairment.